2007
DOI: 10.1097/01.shk.0000238066.00074.90
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Adenosine on Functions of Polymorphonuclear Leukocytes From Patients With Septic Shock

Abstract: Inasmuch as polymorphonuclear leukocytes (PMNs) play a major role in antibacterial defense but can also cause substantial tissue injury, drugs are needed which are able to attenuate tissue-toxic PMN reactions without inhibiting bactericidal mechanisms. Adenosine as a retaliatory metabolite is produced in response to metabolically unfavorable conditions like inflammation. However, it is not known whether adenosine can selectively downregulate adverse PMN reactions in sepsis. In this prospective clinical study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
25
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 32 publications
4
25
1
Order By: Relevance
“…Using the model of PF, we determined dose-response curves by incubation of PMNs with increasing concentrations of adenosine. In agreement with previous reports [9], we demonstrated in healthy volunteers that adenosine is a sensitive inhibitor of potentially tissue-toxic PMN H 2 O 2 production elicited by the soluble stimuli TNF-␣ and fMLP. The dose-response curve observed before takeoff was of sigmoidal shape and values determined for half-maximal and maximum inhibition were well in the range of those reported for healthy PMNs by others [22].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Using the model of PF, we determined dose-response curves by incubation of PMNs with increasing concentrations of adenosine. In agreement with previous reports [9], we demonstrated in healthy volunteers that adenosine is a sensitive inhibitor of potentially tissue-toxic PMN H 2 O 2 production elicited by the soluble stimuli TNF-␣ and fMLP. The dose-response curve observed before takeoff was of sigmoidal shape and values determined for half-maximal and maximum inhibition were well in the range of those reported for healthy PMNs by others [22].…”
Section: Discussionsupporting
confidence: 94%
“…In several in vitro and animal experimental studies, endogenously produced adenosine regulates the function of the innate and adaptive immune systems via targeting virtually every cell type involved in orchestrating the inflammatory response [9,16]. Adenosine controls a wide range of physiologic responses by binding to and activating 4 cell surface adenosine receptors, named A1, A2 A , A2 B , and A3 [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These receptors are classified in four types named A 1 , A 2A , A 2B , and A 3 -all of which are members of G protein-coupled family of receptors [5,7]. Indeed, of all known nucleosides, adenosine is the best characterized immunomodulator, showing anti-inflammatory effects [8] that are related to the inhibition of neutrophil migration and oxygen metabolite production [9][10][11]. Protective effects of adenosine and adenosine receptor agonists have also been shown in different models of inflammatory disease including asthma [12], inflammatory bowel disease [13], endotoxin-mediated shock [14], rheumatoid arthritis [15], sepsis [16], and wound healing [17].…”
Section: Introductionmentioning
confidence: 99%
“…In animal models, A2AR agonists can prevent death from LPS or sepsis (8). Adenosine or A 2 A agonists are reported to inhibit the potentially tissue-toxic H 2 O 2 production elicited by soluble inflammatory mediators in patients with septic shock (9). On the other hand, it is reported that A2AR knockout mice are protected from the lethal effect of sepsis and exhibit improved bacterial clearance compared with wild-type animals (10).…”
mentioning
confidence: 99%